Market research methods in the sports industry : managing sports brands - S̆eric, Neven; Ljubica, Jasenko (Emerald Publishing Limited, 2025)
Whether professional or amateur, sports businesses must develop their brand and image to meet the expectations of a diverse environment, consisting of fans, sponsors, and other stakeholders. The value and instruments of market research can provide the required resources for sports businesses to realize their plans. In this second edition of Market Research Methods in the Sports Industry, Neven Šerić and Jasenko Ljubica provide a comprehensive elaboration of market research methods used by sports businesses. Identifying and explaining the most effective uses of market research, drawing upon a range of updated, real-life case studies, this updated edition brings new chapters and case studies specifically focused on creation and management of sports brands. The application of the methods presented in this book, ranging from the simplest - monitoring the environment- to the most complex sampling methods, can significantly contribute to the development of sports businesses by increasing the number of members, sponsors, followers and fans. Market Research Methods in the Sports Industry is invaluable for researchers, educators and students of Sports Management and Marketing, and it will also prove useful to sporting professionals seeking to gain a competitive edge in the market.